Status and determinants of health services utilization among elderly migrants in China - Xiaofang Zhang; Bin Yu; Tiantian He; Peigang Wang (BMC, 2018)
Abstract Background The household registration system in China places migrants in a vulnerable status regarding access to local public services, including limited access to health services. Most studies on migrants' health services utilization targeted on working-age migrants, and there has been a paucity of studies conducted among elderly migrants. This study aims to investigate the status of health services utilization and its influential factors among elderly migrants. Methods Data (13,043 participants, 52.4% male, mean age 66.22 ± 6.20) were derived from the 2015 Migrant Dynamics Monitoring Survey. The outcome variable in the study was health services utilization, consisting of doctor visits, hospitalization and local inpatient care. The Behavioral Model of Health Service Use was applied to categorize the influential factors into three components, including predisposing, enabling and need factors. Multivariate logistic regression analysis was used to investigate the influential factors of the three components of health services utilization. Results Of the total sample, 45.5% would visit a doctor when they were ill, 81.8% would prefer to be hospitalized when recommended by doctors, and 71.6% (those who were hospitalized) would choose to receive local inpatient care rather than going back to their hometown. Age, marital status, household income, years of residence, migration range, reasons for migration, size of friend network, health insurance type, local health insurance status and chronic disease status were significantly associated with health services utilization. Conclusion A low level of local health services utilization was observed among elderly migrants. Enabling factors played important roles in promoting health services utilization among elderly migrants. Policy and decision makers may consider improving the capability for elderly migrants to access health services, such as increasing income and providing local health insurance.